FRI0427 The Prevalence of Axial Spondyloarthritis in Patients Presenting with Acute Anterior Uveitis. (15th July 2016) - Sykes, M.; Hamilton, L.; Jones, C.; Gaffney, K.
Abstract : Background: Estimates for the prevalence of axial spondyloarthritis (axSpA) in patients presenting with acute anterior uveitis (AAU) range from 11–28%. However, to date no studies have classified patients according to the MRI-based Assessment of Spondyloarthritis International Society (ASAS) criteria. Objectives: To determine the prevalence of axSpA in patients presenting with AAU and identify new "undiagnosed" cases using contemporary MRI-based classification criteria. Methods: Consecutive adult patients presenting to a university teaching hospital between February 2014 and March 2015 with a diagnosis of non-traumatic, non-infective AAU were invited to participate. Patients with a pre-existing diagnosis of axial SpA or another underlying cause of AAU (e.g. sarcoidosis) were not evaluated further. Patients who reported chronic back pain commencing before age 45 were evaluated clinically by an experienced rheumatologist and investigated with laboratory tests and magnetic resonance imaging (MRI). Those patients newly diagnosed with axSpA were classified according to ASAS criteria and the burden of disease recorded. Results: Two hundred and forty-one of 366 patients responded; 57 had a pre-existing diagnosis of axSpA, 77 others fulfilled the study eligibility criteria and 73 (95%) completed the study. Sixteen patients (22%) were diagnosed with axSpA according to the ASAS definition of a positive MRI (12 sacroiliac, 4 spinal). Including those with a previous diagnosis, the minimum prevalence of axSpA in patients presenting with AAU was 19.9%; of these 22% were previously undiagnosed. The median age of "new" axSpA patients was 54 (IQR 41.5 – 58) and 8 (50%) were female. Nine patients (56%) were HLA-B27 positive; 31.3% had a raised CRP. The median duration of back pain was 20.5 years (IQR 17–30.25), and median number of episodes of AAU prior to the diagnosis of axSpA was 3 (IQR 1–7). The median duration of back pain at the time of first episode of uveitis was 15.5 years (IQR 8.5–20.5). Amongst the undiagnosed cases, 6.3% of patients had a pre-existing diagnosis of psoriasis, 18.8% inflammatory bowel disease, 12.5% peripheral inflammatory arthritis and 6.3% a family history of axSpA. The mean BASDAI was 3.17 (SD 1.50), spinal pain visual analogue scale 4.31 (SD 2.02), BASMI 1.63 (SD 1.36), BASFI 2.74 (SD 2.20) and BAS-G 4.70 (SD 1.45). Conclusions: This is the first study to use MRI in order to classify patients with AAU and chronic back pain. At least one fifth of patients presenting to secondary care with AAU have an underlying diagnosis of axSpA. There was a significant hidden burden of disease in that 22% of axSpA patients were previously undiagnosed despite having a long duration of symptoms. Patients presenting with AAU should be screened for chronic back pain and referred to a rheumatologist; this represents an opportunity to shorten the diagnostic delay. Acknowledgement: This study was funded by AbbVie Ltd. Disclosure of Interest: M. Sykes Grant/research support from: AbbVie Ltd, L. Hamilton: None declared, C. Jones: None declared, K. Gaffney Grant/research support from: AbbVie Ltd, MSD, Pfizer, Speakers bureau: AbbVie Ltd, MSD, Pfizer, Novartis, UCB